The Google boys: Sergey Brin and Larry Page in their own words - Sergey Brin; Larry Page; George Beahm (ed.) (Noida: Harper Collins, 2015)
"If you want to find something on the World Wide Web, you "Google" it. With its 1 million servers located around the world, the company handles over a billion search requests daily. But when the Internet first came online, people struggled to organize a seemingly infinite amount of information. Enter two computer science graduate students from Stanford, Larry Page and Sergey Brin, and the $229 billion behemoth we now know as Google was born. For the first time, the most thought-provoking, revealing, and inspiring quotes from Google's founders have been compiled into a single book. The Google Boys: Sergey Brin and Larry Page In Their Own Words is a comprehensive guidebook to the inner workings of Google's founders. Hundreds of their best quotes, comprising thoughts on business, management, entrepreneurship, technology, innovation, and life lessons, provide an intimate and direct look into the minds of these modern business icons. They are now highly respected, established figures in the tech industry, but Page and Brin, unlike industry icons like Steve Jobs or Bill Gates, have spent as little time as possible in front of the media. As a result, when Larry Page and Sergey Brin give time to speak, people listen. Carefully. "--
""A collection of direct quotes from Larry Page and Sergey Brin, the founders of Google, on topics related to business, entrepreneurship, and life"--Provided by publisher"--
Keywords: Biography Businessman; Leadership Business; Business Management; Entrepreneurship Busieness; Management; Applied Sciences